Does energy cause ethnic war? : East Mediterranean and Caspian Sea natural gas and regional conflicts /: East Mediterranean and Caspian Sea natural gas and regional conflicts. (2019) - Stergiou, Andreas; Karagianni, Marika
No abstract available